Les Conséquences des Violences sur la Santé | Muriel Salmona | #Resonantes - Association Resonantes (2016)
Muriel Salmona répond à Resonantes sur les conséquences physiques et psychologiques des violences sur la santé. Plus d'informations sur www.resonantes.fr et sur www.memoiretraumatique.org Images : Nicolas Bertrand / Les Nouveaux Messagers Musique : Axel Boucherat
Keywords: care; cours; discipline; pol5480; premier cycle; ressource en ligne; santé; sciences de l'éducation; thématiques; violences

« Gender Equality and Economic Inequality: Impact on Marriage » dans Gender and couple relationships - Coontz, Stephanie (Gender and couple relationships, 2016)
Changes in aggregate marriage rates and in the internal dynamics of individual marriages should be understood as the outcome of two powerful but very different trends in gender and class relations. One trend is the uneven but undeniably dramatic progress toward equality in personal life and cultural values, which has led to widespread repudiation of centuries-old gender hierarchies. The other trend is an equally powerful movement toward growing inequality, insecurity, and unpredictability in economic life, which has resulted in substantial losses for the most historically vulnerable and least-educated sections of the workforce. The ongoing gender revolution interacts with widening economic inequality in complex ways, increasing the benefits of marriage for individuals with higher earning power while increasing the risks of marriage for low-income individuals, especially women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; care; cours; discipline; discours dominant; droits des femmes*; famille; inégalités; mariage; premier cycle; privilèges; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; soc2262; sociologie; systèmes d'oppressions; thématiques; états-unis

A messy trajectory: From medical sociology to crip theory - Egner J. (Research in Social Science and Disability ; 9, 2016)
Purpose The purpose of this paper is to draw attention to the work of sociologists who laid the foundation for queer and crip approaches to disability and to address how queer and crip theory has and can help to re-conceptualize our understandings of health, illness, disability, and sexuality. Methodology/approach This paper is an examination of historical moments and prominent literature within medical sociology and sociology of disability. Sociological and popular understandings of disability and sexuality have often mirrored each other historically. Although this literature review focuses primarily on medical sociology and disability studies literature, some works of scholars specializing in gender studies, sexuality, literature, history, and queer studies are also included Findings In this paper, I argue that the medicalization and pathologization of human differences specifically as it pertains to sexuality and disability within the medical sociological literature have led to constructionist, social model, and feminist critiques. It is these critiques that then laid the foundation for the development of queer and crip theoretical approaches to both disability and sexuality. Originality/value Crip and queer approaches to disability provide a clear call for future sociological research. Few social science scholars have applied queer and crip approaches in empirical studies on disability. The majority of work in this area is located in the humanities and concerned with literary criticism. A broader array of empirical work on the intersection of sexuality and disability from queer/crip perspectives is needed both to refine these postmodern theoretical models and to examine their implications for the complex lived experience that lies at the intersection of sexuality and disability. In queering disability and cripping sexuality and gender, we may be able not only to more fully conceptualize disability, sexuality, and gender as individual social categories, but also to more fully understand the complex intersection of these social locations.
Keywords: EDI; approches et analyses; care; cours; crip; discipline; histoire et politique; premier cycle; queer; ressource en ligne; santé; sciences humaines; sex1920; sociologie; sofia; thématiques

À la rencontre des femmes Autochtones du Québec - Larivière, Widia; Boulanger, Sébastien; Champagne, Julie; Dubois, Christian; Bouchard, Sylvie; Québec (Province). Conseil du statut de la femme (Conseil du statut de la femme, 2016)
L’organisme Femmes Autochtones du Québec et le Conseil du statut de la femme ont uni leur expertise pour mettre en lumière la réalité des femmes autochtones du Québec. Les femmes autochtones et les femmes non autochtones ont une histoire qui leur est propre, des origines différentes et une identité distincte, ce qui ne les empêche pas de nouer des partenariats1 et de nourrir des aspirations communes. Comme par exemple valoriser la parole et l’action des femmes, souhaiter l’autodétermination et la nondiscrimination pour toutes.
Section: 53 pages : illustrations en couleur ; 28 cm.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; care; cours; droits des femmes*; féminisme autochtone; histoire et politique; justice reproductive; pol4105; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques; travail; violences; éducation

« Répartition des tâches domestique et de soins aux enfants. Intentions et pratiques » dans Devenir parents, devenir inégaux: transition à la parentalité et inégalités de genre - Le Goff, Jean-Marie; Lévy, René (Devenir parents, devenir inégaux: transition à la parentalité et inégalités de genre, 2016)
Une enquête dans laquelle des psychologues, des sociologues et des démographes examinent les mécanismes sociaux à l'oeuvre dans la manifestation des inégalités entre les hommes et les femmes au moment de la naissance de leur premier enfant en Suisse romande. Le poids du passé, la répartition des tâches domestiques et l'emploi du temps sont quelques-uns des aspects abordés.
Section: 1 v. (351 p.) : illustrations ; 23 cm
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; care; cours; discipline; europe; inégalités; maternité; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; soc2264; sociologie; suisse romande; systèmes d'oppressions; thématiques; travail invisible

Reproductive and Sexual Health of People with Physical Disabilities: A Metasynthesis - Nguyen, Thi Tu An; Liamputtong, Pranee; Monfries, Melissa (Sexuality and Disability : A Journal Devoted to the Psychological and Medical Aspects of Sexuality in Rehabilitation and Community Settings, 2016)
This article provides an overview on reproductive and sexual health of people with physical disabilities in developed and underdeveloped countries from 1995 to 2011. Based on the metasynthesis approach, the authors reviewed 15 qualitative studies. These studies were searched using Medline, CINAHL, CINAHL (health), ProQuest Central, Google Scholar, Cochrane, Embase, Informit Health, Sciences Direct, Pubmed, Pubmed Health, AAHD (abstracts), ProQuest Journal (sexuality and disability) and were also manually searched. All studies were judged on their qualities using the Critical Appraisal Skills Programme. Reproductive health, sexual attractiveness and experiences, reproductive and sexual health knowledge, and dealing with reproductive and sexual health issues were four main themes that emerged from these studies. This paper proposes a new model to explain the factors that impacted the reproductive and sexual life of people with physical disabilities: internal and external factors. Implications for health and social care are discussed in light of the findings.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; capacitisme; care; cours; discipline; justice reproductive; médecine; métasynthèse; premier cycle; psychologie; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; sexualité; systèmes d'oppressions; thématiques; travail social

Luttes féministes autour du consentement: Héritages et impensés des mobilisations contemporaines sur la gynécologie - Quéré, Lucile (Nouvelles Questions Féministes, 2016)
L'étude des mobilisations françaises de l'année 2014-2015 autour de la gynécologie permet d'interroger les différentes manières dont les mouvements féministes se sont saisis de la notion de consentement. Théorisé par les féministes à propos de la sexualité, le consentement est apparu comme un des principes fondateurs d'une morale sexuelle féministe. Les mouvements de 2014, portés par des militantes de la cause des femmes, (ré)introduisent cette notion dans le cabinet médical, et l'appliquent notamment à l'interaction gynécologique. Cela leur permet d'utiliser la loi française de 2002 sur les droits des patient·e·s comme un outil de politisation du cabinet gynécologique et de remise en cause des pratiques et des discours des soignant·e·s à l'égard des femmes.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; care; cours; discipline; discours dominant; europe; france; inégalités; justice sociale; militance; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; santé; santé des femmes*; sciences humaines; sexisme; sexualité; systèmes d'oppressions; thématiques